AB1091-HPR Sexual Disturbances in Patients with Rheumatoid Arthritis and It's Relation with Disease Activity. (15th July 2016) - Villarreal, L.; Santos-Moreno, P.; Ballesteros, G.; Bello, J.; Castillo, E.; Giraldo, R.; Gomez, D.; Aza, A.; Lopez, A.; Cardozo, A.; Palacio, N.; Castro, C.; et al.
Abstract : Background: Sexuality is an important dimension of personality and human body, therefore any involvement in this area should be considered as important. Sexual disturbances in rheumatoid arthritis (RA) patients are poorly described in literature. Objectives: The aim of this study was to describe sexual disturbances using CIE-10 in population with RA and a possible correlation with disease activity. Methods: A descriptive cross-sectional study was performed in a specialized clinic dedicated to care patients with RA. 1298 patients were included in the study, which were seen by the area of psychology, which information was collected through semi-structured interviews and non-probability sampling. Descriptive epidemiology was applied for continuous variables, using measures of central tendency and dispersion for categorical and qualitative variables by averages and percentages. We used chi2 test to stablish a relationship between disease activity severity and sexual disturbances. Results: Total sample of patients was 1298, 1048 (80%) were women and 250 (19%) were men. Patients had a DAS28 2.6 in average ± 1.1; mean age was 55.1 ± 8.8 years; According to CIE-10 739 patients (57%) had psychological disorders, 279 patients (21%) had sexual and 373 (28%) had sleep disorders. Regarding entire cohort, 338 (26%) of the total of participants reported any sexual disturbances. Regarding women, 421 (40%) reported no sexual activity, while 627 (67%) reported sexual activity; from reporters of sexual activity 377 (60%) reported satisfactory sexual activity, while 101 (16%) reported no-satisfactory sexual activity, 49 (7%) reported lack or loss of sexual desire, 86 (13%) reported dyspareunia, and 14 (2.9%) orgasmic dysfunction. Regarding men, 77 (30%) of men reported no sexual activity, while 173 (69%) reported sexual activity; of these, 21 (12%) premature ejaculation, 85 (49%) reported satisfactory sexual activity, 23 (13%) reported no-satisfactory sexual activity, 10 (5%) reported lack or loss of sexual desire, 28 (16%) orgasmic dysfunction, 6 (3%) reported dyspareunia. When we analized these results with any factor that could precipitate any sexual disturbance (infidelity, wrong information about sexuality, insecurity in the sexual role, and biological or physical causes) we found that 117 of 338 patients with any sexual disturbance had insecurity in the sexual rol and this relationship was statistically significant (p<0.00). The relationship between having a sexual disturbance and disease activity severity was not statistically significant. Conclusions: We found that patients with AR a high percentage reported not having any sexual activity and between patients with sexual activity there are many (one fourth) reporting any sexual disturbances. The level of disease activity has no relationship with having a sexual disturbance, but having any sexual disturbance had relationship with insecurity in the sexual role. Disclosure of Interest: None declared